Genetic Background of von Willebrand Disease: History, Current State, and Future Perspectives - Zolkova, Jana; Sokol, Juraj; Simurda, Tomas; Vadelova, Lubica; Snahnicanova, Zuzana; Loderer, Dusan; Dobrotova, Miroslava; Ivankova, Jela; Skornova, Ingrid; Lasabova, Zora; Kubisz, Peter; Stasko, Jan (Seminars in Thrombosis and Hemostasis, 2020)
Sequencing of the gene encoding for von Willebrand factor (VWF) has brought new insight into the physiology of VWF as well as its pathophysiology in the context of von Willebrand disease (VWD). Molecular testing in VWD patients has shown high variability in the overall genetic background of this condition. Almost 600 mutations and many disease-causing mechanisms have been described in the 35 years since the VWF gene was identified. Genetic testing in VWD patients is now available in many centers as a part of the VWD diagnostic algorithm. Molecular mechanisms leading to types 2 and 3 VWD are well characterized; thus, information from genetic analysis in these VWD types may be beneficial for their correct classification. However, the molecular basis of type 1 VWD is still not fully elucidated and most likely represents a multifactorial disorder reflecting a combined impact of environmental and genetic factors within and outside of VWF. Regarding sequencing methods, the previous gold-standard Sanger sequencing is gradually being replaced with next-generation sequencing methods that are more cost- and time-effective. Instead of gene-by-gene approaches, gene panels of genes for coagulation factors and related proteins have recently become a center of attention in patients with inherited bleeding disorders, especially because a high proportion of VWD patients, mainly those with low VWF plasma levels (type 1), appear to be free of mutations in VWF. Whole-exome sequencing (WES) and whole-genome sequencing (WGS) are accessible in a very limited number of laboratories. Results from these studies have presented several genes other than VWF or ABO possibly affecting VWF levels, and such findings will need further validation studies.
Keywords: von Willebrand disease; von Willebrand factor; genetic background; genetic testing